Christian faith and modern democracy: God and politics in the fallen world - Kraynak, Robert P. (Frank M. Covey, Jr. Loyola lectures in political analysis, 2001)
Why modern liberal democracy needs God -- The illiberal and undemocratic Christian tradition -- The opening of Christianity to democracy and human rights -- Rethinking Christian politics : the two cities in the modern age -- The earthly city : constitutional government under God